From Scores to Self-Confidence: Reflective Learning in English Professional Development for In-Service Teachers - Rakerda, Hilda; Wulansari, Dini (Institut Agama Islam Negeri Parepare, 2026)
Professional development programs for in-service English teachers often emphasize assessment outcomes while overlooking teachers’ reflective experiences and professional confidence. This study examines how reflection links assessment-oriented training to teachers’ shift from performance-focused learning toward reflective and developmental professional growth. Employing a qualitative single instrumental case study design, data were collected from 20 experienced in-service teachers through reflective writings, test results, semi-structured interviews, and WhatsApp reflections. The data were analyzed using thematic analysis informed by reflective practice, self-efficacy, and sociocultural theories. The findings reveal that reflective engagement shifted teachers from test performance toward developmental learning. This process strengthened teachers’ self-confidence, encouraged them to reconstruct their identities as active language learners despite their long teaching experience, and fostered renewed emotional engagement with English learning. The study suggests that professional development should integrate structured reflective practices to move beyond score-oriented evaluation toward sustainable teacher growth and lifelong learning.